Young adults' attachment styles and beliefs about the "true love" - Kamenov, Željka; Grgičević, Iva (2006)
During their lives, people show different attachment styles in their close relationships, depending on inner working models about themselves and others they have formed in childhood. These working models reflect on two attachment dimensions – anxiety and avoidance. Depending on the level of anxiety and avoidance in their romantic relationships, people show one of four attachment styles: secure, preoccupied, dismissive and fearful (Bartholomew, 1990). People also have different beliefs about &laquo ; true love&raquo ; - what true love is, how difficult it is to find it, what does one need to obtain it or what has to be done in order to develop and maintain it. Most of these beliefs are misconceptions about love and could lead to dysfunctional emotional and behavioral consequences (Milivojevic, 2002). When in love, every person would like that his/her conception about love would become a reality. If this conception is actually a misconception, a person may conclude that his/her relationship does not represent true love. He/she may become unsure and anxious about the relationship or even may leave the partner and try to find a better one. The purpose of this study is to determine the level of dysfunctional beliefs about love among young adults and to relate them with their style of attachment with romantic partners. This was analyzed in the context of participants’ gender, age, previous experiences, and satisfaction with current relationship. The sample of students from University of Zagreb was tested with two instruments: Beliefs about true love questionnaire (Milivojevic, 1995) and Experiences in Close Relationships Inventory (Brennan et al., 1998). Results have shown complex relations between the level of misconceptions about the true love, the attachment style, and satisfaction with current relationship, leading to a conclusion that people having secure attachment with their romantic partners have less misconceptions about love and are more satisfied with their relationship. Results on the anxiety and avoidance dimension of attachment were differently related to beliefs about true love, which may help to predict the behavioral consequences of unfulfilled beliefs and expectations from a romantic relationship. The implications for the cognitive therapy are discussed.
Projekt MZOS
ENG